(untitled) (Journal of Bangladesh Academy of Sciences, 2015)
The radioactivity concentrations of 24 samples of soil and sand sediments from Coxs Bazar were determined using high purity germanium detector. The results of 226Ra, 232Th and 40K in the soil samples were found to vary from 15.34 ± 1.66 to 33.70 ± 2.08 Bq/kg, 30.09 ± 3.62 to 58.06 ± 4.23 Bq/kg and 379.99 ± 33.43 to 755.26 ± 38.03 Bq/kg, respectively. For sand samples the activity concentrations were between 8.98 ± 1.49 to 31.33 ± 2.04 Bq/kg, 16.82 ± 3.24 to 63.28 ± 4.37 Bq/kg and 252.42 ± 31.72 to 565.72 ± 35.78 Bq/kg, respectively, for sediment samples values were 13.90 ± 1.64 to 38.41 ± 2.19 Bq/kg, 37.94 ± 3.82 to 51.92 ± 4.11 Bq/kg and 367.70 ± 33.28 to 665.05 ± 36.97 Bq/kg, 367.70 ± 33.28 to 665.05 ± 36.97 Bq/kg, respectively. The absorbed dose rate of soil, sand and sediment samples were found as 79.98, 77.17, and 57.86 nGy/h, respectively. Outdoor annual effective doses were 0.49, 0.47 and 0.36 mSv/y. Journal of Bangladesh Academy of Sciences, Vol. 39, No. 2, 233-240, 2015